Specially Treated Aramid Fiber Stabilized Gel‐Emulsions: Preparation of Porous Polymeric Monoliths and Highly Efficient Removing of Airborne HCHO. Issue 16 (3rd July 2017) - Liu, Jianfei; Chen, Xiangli; Wang, Pei; Fu, Xuwei; Liu, Kaiqiang; Fang, Yu
Abstract : Porous monoliths with densities as low as 0.06 g cm −3 are prepared by taking acidified aramid‐fiber‐based gel‐emulsions as templates. The preparation process is environmentally benign because the widely used energy‐ and time‐consuming freezing drying and supercritical drying methods are totally avoided. Moreover, the monoliths as prepared show unprecedented adsorptions to formaldehyde. Abstract : Porous polymeric monoliths with densities as low as ≈0.060 g cm −3 are prepared in a gel‐emulsion template way, of which the stabilizer employed is a newly discovered acidified aramid fiber that is so efficient that 0.05% (w/v, accounts for continuous phase) is enough to gel the system. The porous monoliths as obtained can be dried at ambient conditions, avoiding energy‐consuming processes. Importantly, the monoliths show selective adsorption to HCHO, and the corresponding adsorption capacity (M6 ) is ≈2700 mg g −1, the best result that is reported until now. More importantly, the monoliths can be reused after drying.